High Inflammatory Factor Levels Increase Cardiovascular Complications in Diabetic Patients Undergoing Coronary Artery Bypass Grafting. (21st May 2022) - Chen, Jie; Wu, Qiyong; Shi, Haifeng; Zhang, Yong; Wang, Tao; Yin, Ruohan; Pan, Changjie
Abstract : Objective . To investigate the association between inflammation and clinical outcomes of coronary artery bypass grafting (CABG) in diabetic patients. Methods . A total of 300 diabetic patients with coronary heart disease who underwent CABG were selected. Patients were divided into a group with cardiovascular events (32 in the MACCE group) and a group without cardiovascular events (268 in the non-MACCE group) according to whether cardiovascular events occurred within 30 days. The differences in clinical parameters; serum levels of TNF- α, IL-6, IL-18, IL-1 β, and CRP; factors associated with the occurrence of MACCE; and risk factors affecting the midterm all-cause mortality of patients were compared between the two groups. Results . The serum levels of TNF- α, IL-6, IL-18, and CRP in the MACCE group were significantly higher than those in the non-MACCE group (p < 0.05 ). Gender, smoking, hyperlipidemia, duration of diabetes, and levels of TNF- α, IL-6, IL-18, and CRP were closely related to the occurrence of MACCE. The Kaplan-Meier survival analysis evaluation results showed that the levels of IL-6 and CRP significantly affected the midterm all-cause mortality rate (p < 0.05 ). Multivariate Cox regression analysis showed that the advanced age, hypertension, hyperlipidemia, long duration of diabetes, elevated serum IL-6, and CRP levels could be used as risk factors for midterm all-cause mortality. Conclusions . Inflammation levels in diabetic patients are associated with complications and midterm all-cause mortality in patients undergoing coronary artery bypass grafting.